Characterization of three GEM chambers for the SBS front tracker at JLab Hall A. Issue 9 (3rd October 2018) - Re, L.; Bellini, V.; Brio, V.; Cisbani, E.; Colilli, S.; Giuliani, F.; Grimaldi, A.; Librizzi, F.; Lucentini, M.; Mammoliti, F.; Musico, P.; Noto, F.; et al.
ABSTRACT: A new Large-Acceptance Forward Angle Spectrometer [Super Bigbite Spectrometer (SBS)], is under development for the upcoming experiments in Hall A at the Thomas Jefferson National Accelerator Facility (Virginia, USA), where a longitudinally polarized (up to ) electron beam up to 12 GeV energy is now available. The excellent beam intensity (up to 100  A), combined with innovative polarized targets, will provide luminosity up to, opening interesting opportunities to investigate unexplored aspects of the inner structure of the nucleons. In one of the most demanding configuration, the new spectrometer will consist of a dipole magnet, one front charged particle tracker, two identical proton polarimeters with related back trackers and a segmented hadron calorimeter. The front tracker, placed just after the dipole magnet, consists of up to six layers of large area GEM (Gas Electron Multiplier) chambers ( ); each chamber is made by three adjacent GEM modules of active rectangular area (18 modules as a total). We have chosen the GEM technology in order to optimize spatial resolution (∼80 mm), high hit rate ( ), cost/performance and high radiation hardness. We present the main features of the SBS front tracker and its GEM detectors and, finally, we discuss the ongoing tracker commissioning at JLab and show some representative test results.